Blockchain 3.0 applications survey - Di Francesco Maesa, Damiano; Mori, Paolo (Journal of parallel and distributed computing, 2020)
In this paper we survey a number of interesting applications of blockchain technology not related to cryptocurrencies. As a matter of fact, after an initial period of application to cryptocurrencies and to the financial world, blockchain technology has been successfully exploited in many other different scenarios, where its unique features allowed the definition of innovative and sometimes disruptive solutions. In particular, this paper takes into account the following application scenarios: end-to-end verifiable electronic voting, healthcare records management, identity management systems, access control systems, decentralized notary (with a focus on intellectual property protection) and supply chain management. For each of these, we firstly analyse the problem, the related requirements and the advantages the adoption of blockchain technology might bring. Then, we present a number of relevant solutions proposed in the literature both by academia and companies. •Survey of five selected applications Blockchain 3.0 applications.•Problem definition, Blockchain based advantages, case studies for each application.•Electronic voting, healthcare records, IM, AC, decentralized notary, supply chain.